Conjugate‐Base‐Stabilized Brønsted Acids as Asymmetric Catalysts: Enantioselective Povarov Reactions with Secondary Aromatic Amines1. Issue 52 (8th November 2013) - Min, Chang; Mittal, Nisha; Sun, Diana X.; Seidel, Daniel
<x xml:space="preserve">Abstract</x> Caught in the act: A new concept for asymmetric Brønsted acid catalysis is presented. Compounds containing an acidic functionality in addition to an anion recognition site act as powerful conjugate‐base‐stabilized Brønsted acid catalysts. This strategy was applied to the first catalytic enantioselective three‐component Povarov reaction of indoline and other secondary aromatic amines (see scheme; M.S.=molecular sieves).<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>